'Harbour Dwarf' Nandina (Nandina domestica): Noninvasive in South Florida and Recommended with Caution in Central and North Florida - Gary W. Knox; Sandra B. Wilson (EDIS)
ENH1158, a 3-page illustrated fact sheet by Gary W. Knox and Sandra B. Wilson, describes this noninvasive selection of nandina, a short, dense, low-growing, evergreen shrub effective as a groundcover — ornamental characteristics, uses, culture, and history. Includes additional sources of information. Published by the UF Department of Environmental Horticulture, February 2010.